Foreign exchange exposure of Singapore companies - Au, Gregory Chee Hoe (2008)
This study explores the foreign exchange exposure of Singapore companies. Based on models in similar studies done on the subject, a statistical analysis was done to examine whether Singapore companies are vulnerable to foreign exchange fluctuations.